Circulating microRNAs as a potential biomarker for osteoporosis in patients with type 2 diabetes mellitus: a retrospective clinical study - Li, Yuqi; Gan, Lu; Zhao, Dan; Lei, Hong; Sha, Liping (Frontiers in Endocrinology, 2025)
ObjectiveBy analyzing the expression levels of circulating microRNAs (miRNAs) in patients with type 2 diabetes mellitus (T2DM) and its correlation with diabetic osteoporosis (DOP), this study aims to identify potential biomarkers for the early prediction and screening of DOP.MethodsA total of 120 patients with T2DM who received treatment in the endocrinology outpatient/inpatient department between January 2023 and June 2024, along with 90 healthy volunteers, were enrolled in this study. Based on the bone mineral density (BMD), the 120 T2DM patients were divided into three groups: normal group (54 cases), osteopenia group (38 cases), and osteoporosis group (28 cases). The differences in clinical data, laboratory test indicators and miRNA expression differences among the three groups were statistically analyzed, and the high-risk factors for DOP in T2DM patients were analyzed.ResultsCompared to healthy volunteers, patients with T2DM demonstrated significantly decreased levels of P1NP and miR-219a-5p, alongside elevated levels of β-CTX, miR-188-3p, and miR-19a/b. Additionally, miR-335-5p levels were notably reduced in T2DM patients. Among these markers, significant differences were observed in the expression levels of P1NP, β-CTX, and miRNA in T2DM patients. Further analysis revealed distinct expression patterns of miR-188-3p, miR-335-5p, and miR-19a/b across the three T2DM subgroups (osteoporosis, osteopenia, and normal bone density groups). Specifically, miR-188-3p levels were 10.34 ± 1.26 in the osteoporosis group, 8.35 ± 1.33 in the osteopenia group, and 6.55 ± 1.18 in the normal group. Similarly, miR-335-5p levels were 0.44 ± 0.14, 0.67 ± 0.16, and 0.88 ± 0.15, respectively, while miR-19a/b levels were 4.04 ± 1.41, 3.19 ± 1.21, and 2.47 ± 1.24, respectively (P < 0.001 for all comparisons). These miRNAs also exhibited significant correlations with BMD at the hip and lumbar spine (P < 0.001 or P = 0.001), highlighting their potential role in bone metabolism and osteoporosis risk in T2DM patients.ConclusionsThe results suggest that the circulating levels of miR-188-3p, miR-335-5p, and miR-19a/b are significantly associated with the occurrence of DOP in T2DM patients. These miRNAs show potential as biomarkers for the early diagnosis of DOP.